THE EFFECT OF COLORING ACTIVITIES WITH GRADATION TECHNIQUES ON CHILDREN'S CREATIVITY IN GROUP B - Ningsih, Sulastya; Sodik, Nurul Aini MM; Sumirat, Elva M; Bangol, Mega Permatasari (PG PAUD Universitas Negeri Surabaya, 2025)
This study aims to examine the effect of coloring activities using gradient techniques on the creativity of Group B children at KH Dewantoro Pembina State Kindergarten, Gorontalo Indonesia. An experimental method with a one-group pretest–posttest design was employed. The study population consisted of Group B children at the Kindergarten, and a sample of 17 children from Group B3 was selected through purposive sampling. Data were collected using observation, documentation, and performance tests. The instrument used to measure children’s creativity comprised five indicators: fluency, flexibility, elaboration, persistence, and originality. Data were analyzed using a paired-sample t-test. The results revealed that coloring activities using gradient techniques significantly enhanced children’s creativity, as indicated by an increase in the mean pretest score from 39.55 to 75.73 in the posttest. Hypothesis testing using SPSS software produced a two-tailed significance value of 0.000, which is less than the 0.05 threshold. Therefore, the alternative hypothesis was accepted. It can be concluded that coloring activities employing gradient techniques are effective in improving children’s creativity.